LITHOSPHERIC STRUCTURE OF THE TESZ IN POLAND BASED ON MODERN SEISMIC EXPERIMENTS - Guterch A.; Grad M. (My University, 2006)
This paper presents the results of seismic investigations on the structure of the lithosphere in the area of the Trans-European Suture Zone (TESZ) in Poland that is located between the southwestern margin of the East European Craton (EEC) to the north-east, the West and Central European Palaeozoic Platform (PP) to the south-west and the Carpathians to the south. Based on results of the modern POLONAISE'97 and CELEBRATION 2000 projects, as well as older profiles, models are presented for the configuration and extent of different crustal types. In the investigated area, the EEC has a relatively uniform crustal thickness of 40 to 50 km with its three-layered crystalline crust displaying P-wave velocities of 6.1-6.4, 6.5-6.8 and 6.9-7.2 km/s in the upper, middle and lower parts, respectively. The Variscan consolidated crust is covered by 1-2 km thick sediments and consists of two layers with velocities of 5.6-6.3 and 6.5-6.65 km/s. In the Carpathians, sediments reaching to depths of some 20 km and are characterized by velocities of <5.6-5.8 km/s, whilst the underlying two-layered crystalline crust displays velocities of 6.0-6.2 and 6.5-6.9 km/s. The crust of the TESZ can be divided into the Małopolska, Kuiavia and Pomerania blocks that are overlain by up to 9-12 km thick sediments having velocities <5.4 km/s. In the area of the TESZ, the upper part of the consolidated crust has to depths of 15-20 km relatively low velocities of <6.0 km/s and is commonly regarded as consisting of deformed and slightly metamorphosed Early Palaeozoic sedimentary and volcanic series. In this area the middle and lower crust are characterized by velocities in the range of 6.3-6.6 km/s and 6.8-7.2 km/ s, respectively, that are comparable to the EEC. Based on the dense network of seismic profiles the map of the depth to Moho is given for the area of Poland. Uppermost mantle reflectors occur about 10 to 15 kin below the Moho whereas the deepest reflectors are recorded at depths of 90 km. Future investigations ought to aim at an integrated geological-geophysical program, including deep near-verical reflection- seismic profiling and ultimately the drilling of deep calibration boreholes.
Keywords: CELEBRATION 2000; CRUSTAL STRUCTURE; DEEP SEISMIC SOUNDINGS; MANTLE REFLECTORS; POLONAISE'97; TRANS-EUROPEAN SUTURE ZONE